Nhà tuyển dụng cần sinh viên chuyên ngành thư viện-thông tin học biết kỹ năng gì? - Bùi, Hà Phương (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Mentions some skills, indispensable to students of LIS specialty; analyzes employers' demands on these skills from them on the basis of secondary document sources; Sets forth some measures to enhance students' skills for satisfying employers' demands.